Ain-Shams Journal of Anesthesiology - Hassan, Bahaa El-Din Ewees; El-Shaer, Ahmed Nagah; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
As of 23 October 2023, Ain-Shams Journal of Anesthesiology is not accepting new submissions. The journal will no longer be published by Springer Nature as of 1 January 2024. New submissions should be submitted to https://asja.journals.ekb.eg. Any enquiries regarding new submissions can be sent to msalah@sti.sci.eg Ain-Shams Journal of Anesthesiology is an open access, peer-reviewed journal that encompasses all aspects of technical and clinical studies within the fields of anesthesiology, intensive and critical care management, trauma, and pain management. The journal explores efficacy and comparative studies, and includes health-related, ethical, and social issues associated with the subject; articles with clinical interest and implications will be given preference.
Keywords: Surgery; Critical care medicine; Surgery; Intensive Care Medicine